2020
DOI: 10.47836/pjst.28.s2.05
|View full text |Cite
|
Sign up to set email alerts
|

Regression Equation between Required Force and Lumbar Load of Caregiver in Supporting Standing-up Motion via Computational Musculoskeletal Simulation

Abstract: Caregivers experience low back pain because of patient handling such as supporting standing-up. The lumbar load of a caregiver depends on the required force for patient handling motions. If the relationship between the required force and the lumbar load is quantitatively clarified, it may be useful for preventing low back pain in caregivers. In this study, we investigated the quantitative relationships between the required force and lumbar loads such as vertebral stress and muscle activity in supporting standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Lee et al revealed that the COP shifted to the left side when the right foot was placed forward [ 23 ]. Moreover, previous studies have shown that shoe-type force sensors could be used to recognize occupational postures, including different foot positions [ 24 , 25 ], and to monitor trunk movement, lumbar load, and arm movement during manual handling [ 19 , 25 , 26 , 27 ]. From these findings, we hypothesized that foot position can be estimated on the basis of the distribution of the ground reaction force on the foot that is obtained from shoe-type force sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al revealed that the COP shifted to the left side when the right foot was placed forward [ 23 ]. Moreover, previous studies have shown that shoe-type force sensors could be used to recognize occupational postures, including different foot positions [ 24 , 25 ], and to monitor trunk movement, lumbar load, and arm movement during manual handling [ 19 , 25 , 26 , 27 ]. From these findings, we hypothesized that foot position can be estimated on the basis of the distribution of the ground reaction force on the foot that is obtained from shoe-type force sensors.…”
Section: Introductionmentioning
confidence: 99%